2022
DOI: 10.7759/cureus.22378
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Keros Classification of Olfactory Fossa by CT Scan in Qassim Region

Abstract: Endoscopic sinus surgery (ESS) is now the most often utilized surgical procedure for treating chronic sinonasal disorders. Therefore, anatomical knowledge of its variations is required to avoid serious postoperative complications. Thus, careful preoperative examination for patients with a paranasal sinus CT scan is necessary. Our study aims to evaluate Keros types and their incidence by evaluating the olfactory fossa (OF) depth according to the Keros classification on paranasal sinus CT scans in the Qassim reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The OF of Keros III was described in 0.5% of the population, versus 9.5% in our study. Almushayti et al [ 4 ] also found the type II category as the most common followed by type I then type III. Few authors reported that type one was the most common followed by type two then type three [ 7 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The OF of Keros III was described in 0.5% of the population, versus 9.5% in our study. Almushayti et al [ 4 ] also found the type II category as the most common followed by type I then type III. Few authors reported that type one was the most common followed by type two then type three [ 7 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The olfactory fossa (OF) is located along the superior aspect of cribriform plate which varies in shape and depth. This variable measurement of the depth of OF or the height of ethmoid roof is mostly responsible for a greater risk of intracranial infiltration during endoscopic procedures in and around the nasal cavity [ 3 - 5 ]. Previous authors and Kero’s described high risk cases where the depth of OF was between 7–16 mm and categorized them as type III category on paranasal sinus CT scans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the ethmoidal roof, type 3 identified in the studied ovine model, is particularly critical in endoscopic sinus surgery due to its thin cribriform plate, making it the most challenging and significant type. According to the Keros classification, the depth of the olfactory fossa can be categorized into three types: type 1 (1-3 mm), type 2 (4-7 mm), and type 3 (8-16 mm) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Keros type-II is the most common type, followed by type-I and type-III. Patients with Keros type-III, where the olfactory fossa is deepest, are more prone to iatrogenic injury at cribriform plate or lateral lamella of cribriformplate [27]. Since, the base of skull has a slopping shape, it limits the utilization of Keros classification.…”
Section: Discussionmentioning
confidence: 99%